Effect of MXene Loading on the Structure and Electrochemical Performance of Biodegradable PVA/ZnO/MXene/CNC Composite Films - Fernandez, Rudy; Hairul Abral; Ikhwana Elfitri; Syukri Yunus (JURNAL NASIONAL TEKNIK ELEKTRO, 2026)
The growing demand for sustainable materials for flexible electronics and energy storage applications has driven the development of biodegradable composite films with enhanced electrochemical functionality. This study systematically investigates the effect of MXene loading on the structure, morphology, and electrochemical performance of biodegradable PVA/ZnO/MXene/CNC composite films fabricated by aqueous solution casting. The main contribution of this work is the explicit establishment of a relationship between loading, structure, and electrochemical performance for this multicomponent biodegradable film system under controlled processing conditions. Films containing 20%, 25%, and 30% MXene were prepared with constant ZnO and CNC contents and characterized by X-ray diffraction (XRD), field-emission scanning electron microscopy (FESEM), and cyclic voltammetry in 1 M KOH. The crystallinity increased from 20.06% to 27.58% and 44.74% with increasing MXene loading, while FESEM revealed progressively more homogeneous morphology and improved filler dispersion. These structural changes were accompanied by a marked enhancement in electrochemical response, with current density increasing from 425.18 to 876.71 and 1480.25 A/m², and specific capacitance rising from 0.921966 to 1.682536 and 2.860035 F/g for 20%, 25%, and 30% MXene, respectively. The 30% MXene film exhibited the best overall performance, indicating that higher MXene loading within the investigated range promotes more continuous conductive pathways and greater electroactive surface accessibility. These findings provide useful insight for designing biodegradable composite films for sustainable flexible energy-storage applications.